Quantification Des Stocks De Carbone De Trois Pools Clés De Carbone En Afrique Centrale : Cas De La Forêt Marécageuse De La Likouala (Nord Congo) - Bocko, Yannick Enock; Ifo, Suspense Averti; Loumeto, Jean Joël (European Scientific Journal, ESJ, 2017)
The data of carbon stock of central African swamps forests are very few. This study carried out an assessment of the carbon stock of living biomass and coarse woody debris of three biotopes (flooded forest, seasonal flooded forest, and terra firm forest) of Likouala swamp forest (North of Congo). The average of the carbon stock are 190.72±98.7 tC/ha, 39.69±21.24 tC/ha, and 9.45±6.6 tC/ha respectively for above ground, billow ground, and coarse woody debris. The carbon stock of our swamp forest tends to increase generally from the flooded forest to the terra firm forest. In addition, the average of the coarse woody debris carbon stock increases with the increasing of the above ground carbon stock.